Poszanowanie godności osoby zmarłej a działalność funeralna – zagadnienia wybrane - Marczak, Paulina (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
This article presents selected issues concerning the dignity of the deceased in relation to the funeral activity. In the beginning the Author explains several concepts of the dignity of the human, focusing mainly on its definition in constitutional law and its constitutional protection. Coming to the meaning of the dignity of the deceased, the Author notices the lack of its idea in law in force and establishes connection of the notion of the dignity of the human with Article 30 of the Constitution of The Republic of Poland. Afterwards the concept of the dignity of the human is analyzed in comparison to Cemetery and Burial of the Deceased Act of January 31, 1959, noticing lacks in regulations concerning the dignity of the deceased. The Author judges Act amending the Cemetery and Burial of the Deceased Act submitted to the Sejm on October 4, 2013 and its justification, presenting the lack of clarity in the idea of dignity of the deceased. Then the Author evaluates the regulations of the Medical Activity Act of April 15, 2011 and The Cell, Tissue and Organ Recovery, Storage and Transplantation Act of July 1, 2005. The above mentioned issues were completed with the objectives of Directive 2004/23/EC of the European Parliament and of the Council of 31 March 2004 on setting standards of quality and safety of the donation, procurement, testing, processing, preservation, storage and distribution of human tissues and cells and the German Act of Organ Recovery, Storage and Transplantation of November 5, 1997
Keywords: dignity of the deceased; dignity of the human; funeral business; funeral law